An investigation into the behavioral process in Truyen Kieu by Nguyen Du and its translational equivalent in the english version by michael counsell - Nguyễn Thị Thu Hạ (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
This study is carried out to help readers get betterunderstanding ofhow to use the behavioral process, make a comparative analysis between Truyen Kieu by Nguyen Du and its translation equivalent in English by Michael Counsell in the term of behavioral process to identify the semantic and syntactic features and also point out the similarities and differencesof these features of behavioral process between two Vietnamese and English version.